Improving Students' Mathematical Problem-Solving Ability through the Use of External Representations - Amirul Syah; Harizahayu Harizahayu; Annisah Annisah; Emy Yunita Rahma Pratiwi; Gamar Al Haddar (Departement of Mathematics Education, 2023)
This study has the objectives, namely first, to find out whether students' mathematical problem-solving abilities can be improved by using external representations. Second, analyzing student activities in learning mathematics by using external representations. Third, analyzing student responses to learning mathematics by using external representations. This research uses classroom action research (CAR) or classroom action testing (PTK) methods. According to O'Brien in Mulyatiningsih,